A microbiological analysis of coliform bacteria in street food around Universitas Prima Indonesia, Medan - Davin, Radhitya Qowiyyul; Fachrial, Edy; Wienaldi, Wienaldi (Buletin Kedokteran & Kesehatan Prima, 2026)
Background: Street foods, particularly fried snacks, are highly popular among university students due to their convenience and affordability. However, the safety of such foods is a public health concern, as they are susceptible to contamination by coliform bacteria, which can cause gastrointestinal illnesses such as diarrhea. This study aimed to analyze the total coliform bacteria in fried snacks sold around the Universitas Prima Indonesia campus area in Medan as an indicator of food safety. Methods: This descriptive laboratory study analyzed fried snack samples of two types (rissole and filled tofu) collected from six street vendors on Jalan Ayahanda, Medan. Samples were obtained using a simple random sampling technique, resulting in a total of 12 samples. The presence of coliform bacteria was determined using the Most Probable Number (MPN) method with a 3-3-3 tube series, which included a presumptive test using Lactose Broth (LB) medium. Data were analyzed descriptively by comparing results with the standard set by the Indonesian Ministry of Health Regulation No. 2 of 2023 (maximum permissible limit <3.6 MPN/gram). Results: All 12 samples tested negative in the presumptive test, indicated by the absence of gas bubbles in the Durham tubes after 48 hours of incubation. The MPN value for all samples was <3 MPN/gram, confirming they met the required safety standard (<3.6 MPN/gram). Conclusion: Fried snacks sold around the Universitas Prima Indonesia campus were free from coliform bacterial contamination and are considered safe for consumption based on current regulations. Factors such as the high-temperature deep-frying process (>150°C) and adequately maintained vendor sanitation practices likely contributed to the absence of contamination.